Lessons from the Losing: Implications of the COVID‐19 Pandemic for Organizational Diversity Scholarship and Practice - Avery, Derek R. (Journal of Management Studies, 2020)
Organizational profitability and survival are often contingent on the ability to respond to crises effectively (Pearson and Clair, 1998). In this essay, I contend that considering the impact of country composition and culture during the COVID-19 pandemic can enhance our comprehension of the role of diversity during duress. When crises occur, demographic differences tend to be especially salient, as individuals become more attentive to protecting the perceived interests of the in-group, often at the expense of outgroups (King et al., 2010; Krosch et al., 2017). This suggests that more diverse countries may be experiencing more difficulty managing the COVID-19 pandemic than more homogenous countries. Moreover, we know that diversity tends to correspond with higher collective performance when differences are embraced and supported and lower collective performance when diversity is unsupported (e.g., Gonzalez and DeNisi, 2009), at least in part because providing equal opportunity and promoting inclusion increases tolerance for the uncertainty that often accompanies demographic differences (Guillaume et al., 2017). Extrapolating this to the country level suggests that a country’s diversity should correspond in more infections and deaths during a pandemic when its citizens are less tolerant of uncertainty (higher uncertainty avoidance). As a preliminary test of the validity of these conclusions, I conducted a small-scale, country-level examination of the relationship between composition (racioethnic, linguistic, and religious diversity) and culture (Hofstede’s five dimensions; Hofstede, 2001) on COVID-19 incidence and mortality per million residents. For the 66 countries for which full data was publicly available, there are three key conclusions. After controlling for the number of tests per million people, two significant main effects emerged. Incidence (b = 9109.13, p = 0.03) and mortality rates (b = 346.22, p = 0.04) are higher in more ethnically diverse countries, with this form of heterogeneity accounting for roughly 9 per cent of variance in cases and 8 per cent of variance in deaths. Additionally, more individualistic countries (such as the US) have experienced higher death rates (b = 5.88, p < 0.001), with this facet of national culture accounting for nearly 18 per cent of deaths. Looking at the interactions between composition and culture revealed one that was significant – ethnic diversity x uncertainty avoidance (incidence: b = 449.72, p = 0.05, ΔR2 = 0.04; deaths: b = 21.73, p = 0.02, ΔR2 = 0.12). In short, the positive association between ethnic diversity and crisis management efficacy (incidence and deaths) was significant only when uncertainty avoidance was higher among the citizenry. I also re-ran the model including country economic inequality (Gini coefficient; a disparity form of diversity), which eliminated 8 countries due to missing data. The results were largely unchanged and economic diversity exhibited a significant positive effect on cases (b = 293.29, p < 0.01), but not deaths and no interactive effects with culture. The implications for management scholars and practitioners are clear but raise several questions as well. Threats to organizational survival occur with increasing regularity in today’s ever-changing external environment. For instance, Blockbuster went from being a Fortune 500 company to being out of business altogether in less than 5 years. Examining the worldwide COVID-19 pandemic suggests the impact of these threats may be particularly pronounced for entities with greater ethnic diversity. This is especially unfortunate when viewed in concert with the pattern of ethnic and economic disparities in the experiences within such entities. For example, patterns of racioethnic adverse impact in COVID-19 infections starkly resemble that of employment discrimination in the US. Most notably, Hispanic and Black Americans are overrepresented among cases, hospitalizations, and deaths relative to their White counterparts (Moore et al., 2020) – just as they are significantly more likely to perceive themselves on the wrong end of workplace discrimination (Avery et al., 2008). Though less chronicled, COVID-19 also has disproportionally impacted poor people in the US (Vesoulis, 2020), a group who are at a heightened risk of workplace discrimination relative to those of higher economic status (Peterman, 2018). This pattern involving race and ethnicity has led many to question whether the virus itself is somehow racist, but scientists quickly clarified that corresponding discrimination, not identity itself is responsible for these differences (e.g., Wallis, 2020). In short, the impact of crises appear disproportionally more severe when units are more ethnically diverse or have greater income inequality and minorities and the poor within such units find themselves especially more susceptible to harm due to overrepresentation in positions more likely to be impacted (e.g., living in close proximity to others or working in high customer contact roles without remote work options or paid sick leave). The two other significant findings, however, provide some insight as to how this tendency for diversity to coincide in disadvantage might be diminished and open new research possibilities. First, though it did not interact with ethnic diversity, there was a main effect of individualism. The more a culture emphasizes focusing on individual as opposed to collective wellbeing, the greater the negative impact of the threat. This coincides with managerial research on climates for diversity and inclusion emphasizing organizational approaches wherein organizational personnel focus on how each contributor’s uniqueness might enhance the unit’s collective performance through the production of organizational synergies (Dwertmann et al., 2016). Such climates appear to facilitate organizational performance in general (Holmes et al., in press) and future inquiry might consider how they influence organizational functioning during times of crisis and how they might influence the magnitude of disparities on who is harmed. Most notably, do inclusive positions and policies look the same during good times and bad? Moreover, how might inclusive leaders, climates, or policies assist in attenuating the general impact of crises in terms of both severity and inequality? Second, the moderating effect of uncertainty avoidance indicates that greater tolerance for ambiguity might prove particularly useful in helping offset the drawbacks that often accompany diversity (especially during times of crisis) and possibly aid in facilitating prospective benefits. Guillaume et al. (2017) suggested that methods of reducing uncertainty might prove especially useful in optimizing the effects of diversity in organizational settings. An alternative approach might involve helping people be more tolerant of uncertainty instead of expecting it to be attenuated and it appears that organizational culture could help in this regard. We know that societal-level values account for roughly half of the variance in their respective organizational-level equivalents (Dickson et al., 2000) and this contribution cannot be ignored. Nevertheless, organizations have considerable discretion in shaping the remaining 50 per cent of these values among their internal stakeholders. To the extent that employees differ from one another in meaningful ways, it could prove advantageous for the organization to set a tone emphasizing the importance of embracing uncertainty throughout business operations. I encourage theoretical and empirical inquiry to help identify effective means of doing so. For instance, how can organizations offset the effects of regional or national cultures that might prove antagonistic to their employee diversity? Are there ways of leveraging connections with external stakeholders (e.g., partners, municipalities, educational institutions) to help create subcultural ‘bubbles’ that tolerate or even embrace ambiguity within larger cultures (e.g., organizations, cities, states, regions, or countries) that are high in uncertainty avoidance? If not, can organizational climates that support diversity trump the impact of cultures that do not even if the organization is embedded within that culture? A final takeaway involves the relative importance of differing types of diversity in this examination. Differences in ethnicity and economic status appeared more consequential than other forms of difference such as language or religion. Race, ethnicity, and economics appear associated with both the antecedents and consequences of crisis management efficacy during the COVID-19 pandemic. This is not to suggest that the others were inconsequential, but rather that their impact was not significant after accounting for the shared variance with ethnic and economic diversity. Thus, I echo other researchers (e.g., Bell et al., 2011) in calling for greater precision in theory and empirical inquiry when examining diversity. Do the demographic differences that matter in a particular context stay constant or change during times of crisis? How might crises alter patterns of relative influence of different demographic groups? How might faultlines, such as the overrepresentation of people of colour among the poor, accentuate the impact of diversity on crisis severity? With nearly 24 million cases worldwide and a corresponding death toll of more than 800,000 (as of August 2020), there have been no winners in the COVID-19 pandemic. Perhaps the most we can hope for is to learn some vital lessons from this horrific experience that leave us better prepared for future crises. I hope that this commentary proves helpful in that regard.